A thermodynamic model for determination of carbon dioxide solubility and ionic speciation in aqueous alkanolamine solutions - Suleman, H. (Chemical Society of Pakistan, 2017)
A thermodynamic model for determination of carbon dioxide solubility and liquid phase ionic speciation in aqueous alkanolamine solutions has been presented. The explicit model equation is simple in computation and can be solved using a hand-held calculator, yet its structure is derived from thermodynamic theory. The model predicts liquid phase ionic equilibria (bicarbonate, carbonate, hydrogen and alkanolamine based species) in carbon dioxide loaded aqueous monoethanolamine (MEA), diethanolamine (DEA), N-methyldiethanolamine (MDEA) and 2-amino-2-methyl-1-propanol (AMP) solutions. The model shows good correlation with experimental data points and is valid for carbon dioxide loadings of 0.001 to 0.9 for MDEA and AMP, and 0.002 to 0.48 for MEA and DEA, over a wide range of amine concentration, pressure and temperature. The equilibrium model developed in this work is based on and represents 159 data points for CO2 solubility in MEA solutions with 7.9 AARD, 114 selected data points for CO2 absorption in aqueous DEA solutions with 7.1 AARD, 107 reported values for CO2 solubility in MDEA solutions with 9.9 AARD and 136 data values for CO2 absorption in aqueous AMP solutions with 8.4 AARD.